A method for preparing silicon carbide ceramic membrane by reaction-recrystallization integrated sintering

CN122541204BActive Publication Date: 2026-10-09SHENYANG STARLIGHT ADVANCED CERAMICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611048142.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-09
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

但是上述得到的碳化硅陶瓷膜的耐腐蚀性和高温强度有待进一步提高

Benefits of technology

[0006] In view of this, the purpose of this invention is to provide a method for preparing silicon carbide ceramic membranes by integrated reaction-recrystallization sintering. The silicon carbide ceramic membranes prepared by this invention exhibit excellent corrosion resistance and high-temperature strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122541204B_ABST
    Figure CN122541204B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of inorganic ceramic membrane preparation, and provides a method for preparing a silicon carbide ceramic membrane through reaction-recrystallization integrated sintering. The support body slurry, the transition layer slurry and the separation layer slurry are co-extruded into a shape, and then reaction-recrystallization integrated sintering is performed. The procedure of the reaction-recrystallization integrated sintering is as follows: first temperature (600-1400 DEG C) is first raised from room temperature, and first temperature preservation is performed for 2-4 h; second temperature (1400-1800 DEG C) is second raised from the first temperature, and second temperature preservation is performed for 1-2 h; third temperature (1900-2150 DEG C) is third raised from the second temperature, and third temperature preservation is performed for 1.5-2 h. In the process of the reaction-recrystallization integrated sintering, silicon and carbon are sintered in situ to form silicon carbide, and then evaporation-condensation densification is realized at the third temperature, so that the silicon carbide ceramic membrane with excellent corrosion resistance and high-temperature strength is obtained. Meanwhile, the method is simple to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic ceramic membrane preparation technology, and in particular to a method for preparing silicon carbide ceramic membranes by reaction-recrystallization integrated sintering. Background Technology

[0002] Silicon carbide ceramic membranes are widely recognized as a key material with great potential in demanding separation processes in the energy, chemical, and environmental protection fields due to their excellent high temperature resistance, superior thermal shock resistance, extremely high chemical stability (resistance to strong acid and strong alkali corrosion), high filtration flux, and long service life.

[0003] Currently, the preparation of silicon carbide ceramic membranes typically employs an asymmetric structure, consisting of a porous support, a transition layer, and a top separation membrane. Traditional preparation methods often follow a "step-by-step preparation, multiple sintering" approach. For example, patent CN108261928A discloses a pure silicon carbide ceramic membrane element and its preparation method. Step 1, preparation of the support: coarse-grained silicon carbide powder I, polycarbosilane, a binder, and a pore-forming agent are mixed with water to form a slurry, which is then sintered to obtain a pure silicon carbide ceramic membrane support. Step 2, preparation of the transition layer: finer silicon carbide powder II, polycarbosilane, polyvinyl alcohol, and polyacrylic acid are mixed with water to obtain the transition layer. Step 1: A slurry is applied to the inner pore surface of the pure silicon carbide ceramic film support obtained in Step 1 to form a coating layer. Vacuum sintering is then performed to form a transition layer on the inner pore surface of the support. Step 3: Preparation of the surface film: Finer silicon carbide powder III, polycarbosilane, polyvinyl alcohol, and polyacrylic acid are mixed with water to obtain a coating solution. This coating solution is then allowed to flow in the support obtained in Step 2 to form a coating layer on the transition layer. Vacuum sintering is then performed to form a surface film layer on the transition layer.

[0004] Because the support, transition layer, and top separation membrane are prepared and sintered in steps, and are mainly physically stacked and mechanically interlocked, there are abrupt changes in chemical composition and microstructure at the interfaces. These interfaces are prone to becoming stress concentration points and failure sources when subjected to high-temperature thermal cycling, high-pressure backwashing, or highly corrosive media, leading to membrane peeling. Furthermore, the repeated coating, drying, and sintering cycles result in long production cycles, high energy consumption, high costs, and difficulty in controlling the yield.

[0005] To address the aforementioned technical issues, existing technologies have begun to explore integrated sintering. For example, patent CN117820007A discloses a method for preparing and applying a high-throughput silicon carbide ceramic membrane via ultra-low temperature co-sintering. Specifically, coarse silicon carbide aggregate is uniformly mixed with a sintering aid to obtain a mixed powder A. After thoroughly mixing the mixed powder A with a binder, a sheet-like support green body B is formed under a certain forming pressure. After drying the sheet-like support green body B, a support green body C is obtained. The process involves mixing fine silicon carbide powder with a sintering aid and dispersing it uniformly in a dispersion of a certain concentration to obtain a film-forming solution. This solution is then deposited onto a green substrate C via spraying. The substrate is subsequently dried at room temperature (20%–45% humidity) and in an oven at a specific temperature to obtain an asymmetric silicon carbide ceramic film green substrate. This green substrate is then placed in a high-temperature furnace and subjected to an ultra-low temperature co-sintering process according to a specific sintering procedure to obtain a high-throughput silicon carbide ceramic film. However, the corrosion resistance and high-temperature strength of the obtained silicon carbide ceramic film require further improvement. Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a method for preparing silicon carbide ceramic membranes by integrated reaction-recrystallization sintering. The silicon carbide ceramic membranes prepared by this invention exhibit excellent corrosion resistance and high-temperature strength.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing silicon carbide ceramic films by integrated reaction-recrystallization sintering, comprising the following steps: A first silicon carbide powder, a first carbon source, a first silicon source, an organic binder, a first dispersant, a plasticizer, and a first organic solvent are mixed to obtain a support slurry; the mass percentage of the first carbon source in the support slurry is 0.5% to 5%. The second silicon carbide powder, the second carbon source, the second silicon source, and the second organic solvent are mixed to obtain a transition layer slurry. The third silicon carbide powder, the third carbon source, the third silicon source, the second dispersant, and the third organic solvent are mixed to form a separation layer slurry; After the support slurry, transition layer slurry and separation layer slurry are co-formed, they are microwave dried to form a green body in which the support slurry, transition layer slurry and separation layer slurry are stacked in sequence. The green body is subjected to reaction-recrystallization integrated sintering to obtain the silicon carbide ceramic film; The reaction-recrystallization integrated sintering procedure is as follows: The temperature is first raised from room temperature to a first temperature and then kept warm for a first time. The first temperature is 600~1400℃ and the first warming time is 2~4h. The temperature is raised from the first temperature to a second temperature and then kept warm for a second time. The second temperature is 1400~1800℃ and the second holding time is 1~2 hours. The temperature is raised from the second temperature to a third temperature and then held for a third time. The third temperature is 1900~2150℃ and the holding time is 1.5~2h. The particle size of the first silicon carbide powder is greater than that of the second silicon carbide powder, which is greater than that of the third silicon carbide powder.

[0008] Preferably, the support slurry comprises the following components by mass percentage: The first component is 60-65% silicon carbide powder, the first carbon source is 0.5-5%, the first silicon source is 5-10%, the first organic binder is 1-5%, the first dispersant is 0.5-3%, the first plasticizer is 1-5%, and the first organic solvent is 10-20%.

[0009] Preferably, the first silicon carbide powder is α-SiC, and the particle size of the first silicon carbide powder is 20~100μm; the first carbon source includes one or more of carbon black, graphite and phenolic resin; the first silicon source includes silicon powder.

[0010] Preferably, the transition layer slurry comprises the following components in weight percentage: The second component consists of 40-60% silicon carbide powder, 5-30% carbon source, 10% silicon source, and 20-25% organic solvent.

[0011] Preferably, the second silicon carbide powder is α-SiC powder or β-SiC powder, and the particle size of the second silicon carbide powder is 1~10μm; the second carbon source includes one or more of sucrose, phenolic resin and carbon black; the second silicon source includes silicon and / or silica sol.

[0012] Preferably, the separation layer slurry comprises the following components in weight percentage: The third component is 40-50% silicon carbide powder, the third component is 1-10% carbon source, the third component is 15-30% silicon source, the second component is 0.5-10% dispersant, and the third component is 15-25% organic solvent.

[0013] Preferably, the third silicon carbide powder is β-SiC powder, and the particle size of the third silicon carbide powder is 0.05~1μm; the third carbon source includes carbon black and / or phenolic resin; the third silicon source includes one or more of silicon powder, polymethylsilane and vinyl perhydropolycarbosilane.

[0014] Preferably, the co-molding method is one or more of co-extrusion molding, sequential casting molding, and pressure-assisted injection molding.

[0015] Preferably, the reaction-recrystallization integrated sintering is carried out under a protective atmosphere, namely argon.

[0016] Preferably, the heating rates of the first, second, and third heating are independently 1~10℃ / min.

[0017] This invention provides a method for preparing silicon carbide ceramic films by reaction-recrystallization integrated sintering.

[0018] This invention co-forms the support slurry, transition layer slurry, and separation layer slurry, and then performs reaction-recrystallization integrated sintering. During the reaction-recrystallization integrated sintering process, silicon and carbon react and sinter in situ to form silicon carbide, and then evaporation-condensation densification is achieved at a third temperature, resulting in a silicon carbide ceramic film with excellent corrosion resistance and high-temperature strength. Attached Figure Description

[0019] Figure 1 This is a process flow diagram of the preparation method of the present invention; Figure 2 This is a cross-sectional scanning electron microscope image of the tubular silicon carbide microfiltration membrane obtained in Example 1; Figure 3 This is a cross-sectional scanning electron microscope image of the thin-layer asymmetric silicon carbide nanofiltration membrane obtained in Example 3; Figure 4 This is a cross-sectional scanning electron microscope image of the silicon carbide film obtained in Comparative Example 1. Detailed Implementation

[0020] This invention provides a method for preparing silicon carbide ceramic films by integrated reaction-recrystallization sintering, comprising the following steps: A first silicon carbide powder, a first carbon source, a first silicon source, an organic binder, a first dispersant, a plasticizer, and a first organic solvent are mixed to obtain a support slurry; the mass percentage of the first carbon source in the support slurry is 0.5% to 5%. The second silicon carbide powder, the second carbon source, the second silicon source, and the second organic solvent are mixed to obtain a transition layer slurry. The third silicon carbide powder, the third carbon source, the third silicon source, the second dispersant, and the third organic solvent are mixed to form a separation layer slurry; After the support slurry, transition layer slurry and separation layer slurry are co-formed, they are microwave dried to form a green body in which the support slurry, transition layer slurry and separation layer slurry are stacked in sequence. The green body is subjected to reaction-recrystallization integrated sintering to obtain the silicon carbide ceramic film; The reaction-recrystallization integrated sintering procedure is as follows: The temperature is first raised from room temperature to a first temperature and then kept warm for a first time. The first temperature is 600~1400℃ and the first warming time is 2~4h. The temperature is raised from the first temperature to a second temperature and then kept warm for a second time. The second temperature is 1400~1800℃ and the second holding time is 1~2 hours. The temperature is raised from the second temperature to a third temperature and then held for a third time. The third temperature is 1900~2150℃ and the holding time is 1.5~2h. The particle size of the first silicon carbide powder is greater than that of the second silicon carbide powder, which is greater than that of the third silicon carbide powder.

[0021] Unless otherwise specified, the raw materials used in this invention are preferably commercially available products.

[0022] Figure 1 The following is a flowchart of the preparation method of the present invention, in conjunction with... Figure 1 The preparation method of the present invention will be described.

[0023] This invention involves mixing a first silicon carbide powder, a first carbon source, a first silicon source, an organic binder, a first dispersant, a plasticizer, and a first organic solvent (denoted as the first mixture) to obtain a support slurry; the mass percentage of the first carbon source in the support slurry is 0.5-5%. In this invention, the support slurry preferably comprises the following components in the following mass percentages: 60-65% first silicon carbide powder, 0.5-5% first carbon source, 5-10% first silicon source, 1-5% organic binder, 0.5-3% first dispersant, 1-5% plasticizer, and 10-20% first organic solvent. In this invention, the mass percentage of the first silicon carbide powder in the support slurry is preferably 60%, 61%, 62%, 63%, 64%, or 65%; the mass percentage of the first carbon source is preferably 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%; the mass percentage of the first silicon source is preferably 5%, 6%, 7%, 8%, 9%, or 10%; the mass percentage of the organic binder is preferably 1%, 2%, 3%, 4%, or 5%; the mass percentage of the first dispersant is preferably 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%; the mass percentage of the plasticizer is preferably 1%, 2%, 3%, 4%, or 5%; and the mass percentage of the first organic solvent is preferably 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%. In this invention, the first silicon carbide powder is preferably α-SiC; the particle size of the first silicon carbide powder is preferably 20-100 μm, specifically preferably 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or 100 μm. In this invention, the first carbon source preferably includes one or more of carbon black, graphite, and phenolic resin, wherein the graphite is preferably flake graphite. In this invention, the first silicon source preferably includes silicon powder, wherein the particle size of the silicon powder is preferably 300-350 mesh, more preferably 325 mesh. In this invention, the organic binder preferably includes polyvinyl butyral (PVB). In this invention, the first dispersant preferably includes one or more of castor oil phosphate, trioleic acid glyceride, and fish oil. In this invention, the plasticizer preferably includes one or more of dibutyl phthalate (DBP), polyethylene glycol, and glycerin. In this invention, the first organic solvent preferably includes ethanol. In this invention, the first mixing method is preferably ball milling. In this invention, the mass percentage of the first carbon source in the support slurry is 0.5-5%, which is low and is intended to slightly enhance particle bonding in subsequent reactions.

[0024] This invention involves mixing a second silicon carbide powder, a second carbon source, a second silicon source, and a second organic solvent (denoted as the second mixture) to obtain a transition layer slurry. In this invention, the transition layer slurry preferably comprises the following components by mass percentage: 40-60% second silicon carbide powder, 5-30% second carbon source, 10% second silicon source, and 20-25% second organic solvent. Specifically, the mass percentage of the second silicon carbide powder in the transition layer slurry is preferably 40%, 45%, 50%, 55%, or 60%; the mass percentage of the second carbon source is preferably 5%, 10%, 15%, 20%, 25%, or 30%; the mass percentage of the second silicon source is preferably 10%; and the mass percentage of the second organic solvent is preferably 20% or 25%. In this invention, the second silicon carbide powder is preferably α-SiC powder or β-SiC powder. In this invention, the particle size of the second silicon carbide powder is preferably 1-10 μm, specifically preferably 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm. In this invention, the second carbon source preferably includes one or more of sucrose, phenolic resin, and carbon black. In this invention, the second silicon source preferably includes silicon powder and / or silica sol, wherein the solid content of the silica sol is preferably 25-30%. In this invention, the second organic solvent preferably includes ethanol, butanone, and isopropanol, specifically preferably ethanol, an ethanol-butanone mixture, or an ethanol-isopropanol mixture, wherein the mass ratio of ethanol to butanone in the ethanol-butanone mixture is preferably 1:1, and the mass ratio of ethanol to isopropanol in the ethanol-isopropanol mixture is preferably 3:2. In this invention, the particle size of the first silicon carbide powder is greater than the particle size of the second silicon carbide powder. In this invention, the transition layer slurry serves as a bridge connecting the support layer and the separation layer.

[0025] This invention mixes a third silicon carbide powder, a third carbon source, a third silicon source, a second dispersant, and a third organic solvent to form a separation layer slurry. In this invention, the separation layer slurry comprises the following components in weight percentages: 40-50% third silicon carbide powder, 1-10% third carbon source, 15-30% third silicon source, 0.5-10% second dispersant, and 15-25% third organic solvent. In this invention, the mass percentage of the third silicon carbide powder in the separation layer slurry is preferably 40%, 45%, or 50%; the mass percentage of the third carbon source is preferably 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%; the mass percentage of the third silicon source is preferably 15%, 20%, 25%, or 30%; the mass percentage of the second dispersant is preferably 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, or 10%; and the mass percentage of the third organic solvent is preferably 15%, 20%, or 25%. In this invention, when the separation layer slurry preferably also includes a sintering aid, the mass percentage of the sintering aid in the separation layer slurry is preferably 0.5-2%, specifically preferably 0.5%, 1%, 1.5%, or 2%. In this invention, the third silicon carbide powder is preferably β-SiC powder; the particle size of the third silicon carbide powder is preferably 0.05~1μm, specifically preferably 0.05μm, 0.08μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm. In this invention, the third carbon source preferably includes carbon black and / or phenolic resin. In this invention, the third silicon source preferably includes one or more of silicon powder, polymethylsilane (PMS), and vinyl perhydropolycarbosilane (VHPCS), and the particle size of the silicon powder is preferably 100nm. In this invention, when the third silicon source is preferably one or more of polymethylsilane (PMS) and vinyl perhydropolycarbosilane (VHPCS), it is preferable to use both as the third carbon source and the third silicon source simultaneously, without adding a third carbon source. In this invention, the second dispersant preferably comprises one or more of trioleic acid glyceride, castor oil phosphate, and fish oil. In this invention, the third organic solvent preferably comprises one or more of toluene, xylene, and ethanol. In this invention, the sintering aid preferably comprises B4C and / or Al2O3. In this invention, the particle size of the second silicon carbide powder is greater than the particle size of the third silicon carbide powder.

[0026] After obtaining the support slurry, transition layer slurry, and separation layer slurry, the present invention co-forms the support slurry, transition layer slurry, and separation layer slurry, and then performs microwave drying to form a green body in which the support slurry, transition layer slurry, and separation layer slurry are stacked in sequence.

[0027] In this invention, the co-molding method is preferably one or more of co-extrusion molding, sequential casting molding, and pressure-assisted injection molding; this invention does not specifically limit the parameters of co-extrusion molding, sequential casting molding, and pressure-assisted injection molding, and any operation known to those skilled in the art can be used.

[0028] In this invention, the preferred method of co-forming is co-extrusion molding, and the shape of the wet preform obtained by co-forming is preferably tubular or flat.

[0029] In this invention, the preferred method of co-forming is sequential casting, and the shape of the wet blank obtained by co-forming is preferably substrate-type or sheet-type.

[0030] In this invention, the preferred method of co-forming is pressure-assisted injection molding, and the shape of the wet blank obtained by co-forming is preferably honeycomb or irregular columnar.

[0031] In this invention, the equipment used for microwave drying preferably includes a microwave drying tunnel, a box-type microwave dryer, or a tunnel-type continuous microwave drying line.

[0032] In this invention, when the shape of the wet blank obtained by co-forming is preferably tubular or flat, the microwave drying equipment is preferably a tunnel-type continuous microwave drying line. In this invention, the parameters of the tunnel-type continuous microwave drying line include: microwave power preferably 1~2kW, specifically preferably 1kW, 1.5kW, or 2kW; frequency preferably 2450MHz; hot air temperature preferably 60~80℃; and drying time preferably 30~40min.

[0033] In this invention, when the shape of the wet blank obtained by co-forming is preferably honeycomb or irregular columnar, the microwave drying equipment is preferably a box-type microwave dryer.

[0034] In this invention, when the shape of the wet blank obtained by co-molding is preferably substrate-type or sheet-type, the microwave drying equipment is preferably a microwave drying tunnel.

[0035] In this invention, traditional hot air drying is prone to cracking due to uneven shrinkage. Microwave drying utilizes the penetrating heating characteristics of microwaves to perfectly solve the problem of cracking and deformation of thin-walled ceramic film blanks caused by traditional drying methods. It is a key device for achieving fast, uniform, and high-quality drying. Specifically: (1) "High-efficiency drying" that combines internal and external heat: In traditional hot air drying, heat is slowly conducted from the outside to the inside, which is inefficient and uneven. Microwave drying is completely different. It is a "combined internal and external" overall heating method. (2) Overall heating: The core is a microwave magnetron, which can generate high-frequency electromagnetic waves with a frequency of 2450MHz. These electromagnetic waves can directly penetrate the ceramic film blank and interact with the polar molecules (mainly water molecules) inside it. (3) Internal heat generation: Water molecules oscillate and rub at a high speed of 2.45 billion times per second in the microwave field, instantly generating heat and causing the blank to heat up from the inside to the outside. This heating method completely subverts the traditional heat conduction mode. (4) Crack and deformation prevention: Because the entire piece is heated simultaneously, the shrinkage inside and outside the blank is uniform, which fundamentally solves the problem of cracking and deformation caused by stress concentration, and greatly improves the yield. (5) Extremely fast and efficient: The drying speed is even dozens of times faster than that of traditional hot air drying. For example, some data show that microwave drying equipment can quickly reduce the moisture content of the blank from 18-25% to below 3%, significantly shortening the production cycle. (6) Energy saving and environmental protection: The energy acts directly on the water molecules, without the need to heat the air, equipment and other intermediate media, and the thermal efficiency is extremely high. Compared with the traditional method, it can save more than 30% of energy. Moreover, the equipment can be used immediately without residual heat loss and pollution emissions. (7) Intelligent and controllable: Modern microwave drying equipment generally supports PLC automatic control, which can accurately adjust the microwave power, drying temperature and transmission speed. The operation is flexible and simple, and it is easy to realize the automation of the production line.

[0036] After forming a green body with a support slurry, a transition layer slurry, and a separation layer slurry stacked in sequence, the present invention performs reaction-recrystallization integrated sintering on the green body to obtain the silicon carbide ceramic film.

[0037] In this invention, the reaction-recrystallization integrated sintering process is as follows: The temperature is first increased from room temperature to a first temperature, followed by a first heat preservation process. The temperature is raised from the first temperature to a second temperature for a second heat preservation process. The temperature is raised from the second temperature to the third temperature for a third heat preservation.

[0038] In this invention, the reaction-recrystallization integrated sintering is preferably carried out under a protective atmosphere, preferably argon.

[0039] In this invention, the first temperature is 600~1400℃, specifically preferably 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, or 1400℃; the first holding time is 2~4 hours, specifically preferably 2 hours, 3 hours, or 4 hours. In this invention, the first heating rate is preferably 1~10℃ / min, more preferably 1~5℃ / min, specifically preferably 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, or 5℃ / min. In this invention, this stage completely removes organic binders and volatiles from the green body.

[0040] In this invention, the second temperature is 1400~1800℃, specifically preferably 1400℃, 1450℃, 1500℃, 1550℃, 1600℃, 1650℃, 1700℃, 1750℃, or 1800℃; the second holding time is 1~2 hours. In this invention, the second heating rate is preferably 1~10℃ / min, more preferably 3~8℃ / min, specifically preferably 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, or 8℃ / min. In this invention, within this temperature range, the silicon source in the blank (whether free silicon powder or active silicon generated from precursor decomposition) undergoes carbothermic reduction or direct reaction with the carbon source, generating a new β-SiC phase in situ. This process is particularly intense in the transition layer and separation layer, where newly formed, highly active nano-SiC particles fill the gaps between existing SiC particles and become "bridges" connecting the particles. Meanwhile, a small amount of carbon source in the support layer also reacts with SiO2 on the surface of SiC particles or directly with silicon, enhancing the connection between particles.

[0041] In this invention, the third temperature is 1900~2150℃, specifically preferably 1900℃, 1950℃, 2000℃, 2050℃, 2100℃, or 2150℃; the third holding time is 1.5~2h. In this invention, the third heating rate is preferably 1~10℃ / min, more preferably 5~10℃ / min, specifically preferably 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min. In this invention, the smaller, higher surface energy SiC particles (including raw material powder and in-situ generated nano-SiC) in the separation layer and transition layer preferentially evaporate, and then condense and grow at the neck or contact point of the coarse particles. This "recrystallization" process increases the ratio (d / d0) of the particle neck diameter (d) to the particle diameter (d0), forming a robust sintered neck, thereby achieving densification and a significant increase in strength of the film. The key is that, since the three-layer structure undergoes this process simultaneously in the same blank, the material transport crosses the original interlayer interface, allowing the SiC particles between the layers to grow together through a recrystallization mechanism, forming a "seamless connection" similar to metallurgical bonding, which improves the corrosion resistance and high-temperature strength of the silicon carbide ceramic film.

[0042] After the third heat preservation is completed, the present invention preferably further includes cooling, which includes: reducing the temperature to a first temperature at a first cooling rate, and then allowing the furnace to cool naturally to room temperature. In the present invention, the first cooling rate is preferably 5°C / min, and the first temperature is preferably 800°C.

[0043] In this invention, the reaction-recrystallization integrated sintering is preferably carried out in a carbon tube furnace or an induction furnace.

[0044] The method for preparing silicon carbide ceramic films by reaction-recrystallization integrated sintering provided by the present invention will be described in detail below with reference to the embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0045] Example 1: Preparation of tubular silicon carbide microfiltration membrane 1. Raw material preparation: Support slurry: 65wt% α-SiC coarse powder (50μm), 5wt% flake graphite, 10wt% silicon powder (325 mesh), 20wt% organic system (including 5% PVB binder, 2% castor oil phosphate dispersant, 3% DBP plasticizer and 10% ethanol solvent).

[0046] Transition layer slurry: 2μm β-SiC powder as the main skeleton (60wt%), with 5wt% sucrose (as carbon source) and 10wt% silica sol (SiO2·nH2O, as silicon source, solid content of 25~30%) added, as well as 25wt% organic solvent ethanol.

[0047] Separation layer slurry: 50wt% β-SiC fine powder (0.5μm), 10wt% phenolic resin (as carbon source and binder), 15wt% nano-silica powder (~100nm), 25wt% organic system (dispersant glyceryl trioleate 5% and organic solvent toluene 20%).

[0048] 2. Molding: A dual-channel co-extruder is used. The inner channel extrudes the support slurry to form a tubular support wet preform with an outer diameter of 30 mm and an inner diameter of 22 mm. Simultaneously, the outer channel extrudes the transition layer slurry and coats it onto the outer surface of the support wet preform, forming an initial transition layer (approximately 50 μm thick). Then, in the semi-dry state of the initial transition layer, the release layer slurry is uniformly coated onto the interface of the initial transition layer using dip coating or spray coating. The initial thickness of the release layer slurry is 10 μm, forming a complete tubular three-layer gradient structure wet preform.

[0049] The tubular three-layer gradient structure wet blank is dried and cured by microwave in a tunnel-type continuous microwave drying line (microwave power 2kW, frequency 2450MHz, hot air temperature 80℃, drying time 30min) to obtain a dried blank (moisture content reduced to below 3%).

[0050] 3. Sintering: The dried green body is placed in a graphite sintering furnace, and after vacuuming, high-purity argon gas is introduced for protection; the temperature is increased to 600℃ at 2℃ / min and held for 2h, then increased from 600℃ to 1650℃ at 5℃ / min and held for 1h (to carry out the in-situ reaction of Si+C→SiC), and finally increased from 1650℃ to 2050℃ at 8℃ / min and held for 2h (to carry out recrystallization sintering); then the temperature is reduced to 800℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature with the furnace to obtain a tubular silicon carbide microfiltration membrane.

[0051] 4. Results: The outer diameter of the obtained tubular silicon carbide microfiltration membrane is 30 mm and the inner diameter is 22 mm; Figure 2 Here are cross-sectional scanning electron microscope images of the obtained tubular silicon carbide microfiltration membrane, from... Figure 2 It can be seen that there is a continuous gradient transition from the support layer to the separation layer, and a seamless connection; at the same time, the thickness of the transition layer is 50μm and the thickness of the separation layer is 10μm.

[0052] The average pore size of the separation layer of the tubular silicon carbide microfiltration membrane was measured to be 0.2 μm using the bubble compression method.

[0053] The porosity of the tubular silicon carbide microfiltration membrane was 45%, as measured by GB / 39717 2020.

[0054] The three-point bending strength of the tubular silicon carbide microfiltration membrane, as tested according to GB / T 1965, is 85 MPa.

[0055] Water flux testing reference standards: The pure water flux test method is determined in accordance with GB / T 43300-2023 "Test Method for Pure Water Flux of Ceramic Flat Sheet Membrane" and GB / T 32360-2015 "Test Method for Ultrafiltration Membrane".

[0056] Test apparatus and conditions: A tubular ceramic membrane permeation performance testing device was used. The test medium was deionized water (25±1℃, conductivity ≤5 μS / cm), the driving method was nitrogen pressurization, the transmembrane pressure difference was set to 0.1MPa, and the temperature was kept constant during the test.

[0057] Test steps: 1. Before the acid and alkali corrosion resistance test, install the tubular silicon carbide microfiltration membrane element in the test apparatus. Pre-pressurize and run for 30 minutes under a transmembrane pressure difference of 0.1 MPa and a temperature of 25°C until the membrane flux stabilizes, then proceed with the test.

[0058] 2. Under steady-state conditions, collect the water effluent from the membrane filtration side using a graduated cylinder and record the permeate volume within a specified time (usually 5-10 minutes).

[0059] 3. Measuring the effective filtration area of ​​the membrane: For tubular membranes, the filtration area is calculated based on the inner diameter of the membrane tube. The calculation formula is as follows: A=π×d×L (Formula 1); In the formula, A is the effective filtration area of ​​the membrane (m²). 2 ); d is the inner diameter of the membrane tube (m), and in Example 1, d is 22mm = 0.022m; L: effective length of the membrane tube (m).

[0060] 4. Calculate the pure water flux according to Formula 2. J = V / (A × t) (Formula 2); In the formula, J: pure water flux (L·m -2 ·h -1 V: Volume of permeate in time t (L); A: Effective filtration area of ​​the membrane (m²). 2 ); t: permeate collection time (h).

[0061] Comparison of acid and alkali before and after boiling: The acid and alkali corrosion resistance of ceramic membranes was tested according to the standard method. Before testing, the initial pure water flux was measured and recorded as J0. The membrane element was immersed in 1M NaOH solution and 1M H2SO4 solution respectively, and boiled in a boiling water bath for 24 hours, changing the acid and alkali solutions every 8 hours to maintain the concentration. After boiling, the membrane element was repeatedly rinsed with deionized water until neutral, and then soaked in pure water at 25℃ for 24 hours to recover. The pure water flux was measured again following the above steps and recorded as J1.

[0062] The water flux attenuation rate is calculated according to Formula 3: η=(J0-J1) / J0×100% (Formula 3); In the formula, J0: initial pure water flux (before treatment), J1: pure water flux after treatment (e.g., after acid and alkali boiling).

[0063] Formula 3 is a commonly used expression of performance degradation in the field of membrane separation, and it conforms to the calculation method recommended by standard GB / T 32360-2015 "Test Methods for Ultrafiltration Membranes".

[0064] Test results: After boiling in 1M NaOH solution for 24 h, the water flux decreased from the original 3100 LMH to 3007 LMH, with an attenuation rate of approximately 3.0%; after boiling in 1M H2SO4 solution for 24 h, the water flux decreased from the original 3100 LMH to 3035 LMH, with an attenuation rate of approximately 2.1%, both meeting the performance indicator of an attenuation rate of less than 5%.

[0065] In a high-temperature flue gas filtration simulation experiment at 800℃, the membrane structure remained intact after undergoing 10 cycles of rapid cooling and heating (800℃↔ room temperature).

[0066] Example 2: Preparation of a flat-sheet silicon carbide ultrafiltration membrane The difference from Example 1 is that in step 1, the transition layer slurry includes the following components by mass percentage: 60 wt% of 2 μm β-SiC powder as the main skeleton, 5 wt% of sucrose (as a carbon source) and 10 wt% of silica sol (SiO2·nH2O, as a silicon source, with a solid content of 25~30%), and 25 wt% of organic solvent (a mixed solvent of ethanol and butanone, with a mass ratio of 1:1).

[0067] In step 2, during the molding process, the support slurry is extruded to form a flat film support (6 mm thick, with a square channel in the middle having a side length of 2 mm); a transition layer slurry and a separation layer slurry are sequentially cast onto the flat film support, wherein the thickness of the transition layer is 0.5 mm and the thickness of the separation layer is 0.2 mm.

[0068] The obtained flat wet blank was microwave dried in a tunnel-type continuous microwave drying line with the following parameters: microwave power 1.5kW, frequency 2450MHz, hot air temperature 70℃, and drying time 30min.

[0069] In step 3, during the sintering process, the temperature is adjusted from 2050℃ to 1950℃ to obtain a flat silicon carbide ultrafiltration membrane.

[0070] The remaining steps and operations are the same as in Example 1.

[0071] The average pore size of the separation layer of the planar silicon carbide ultrafiltration membrane was measured to be 50 nm using the bubble pressure method, making it suitable for applications such as oil-water emulsion separation.

[0072] Scanning electron microscopy was used to observe the cross-section of the obtained planar silicon carbide ultrafiltration membrane. The results showed that the interlayer bonding was dense and the pore size had a continuous gradient distribution.

[0073] The porosity of the obtained planar silicon carbide ultrafiltration membrane, as measured by GB / 39717 2020, is 45%, and the three-point bending strength of the obtained planar silicon carbide ultrafiltration membrane, as tested by GB / T 1965, is 80 MPa.

[0074] The flat-sheet silicon carbide ultrafiltration membrane was boiled in 1M NaOH or 1M H2SO4 solution for 24 hours. No peeling or bubbling of the membrane layer was observed. The water flux was tested according to GB / T 43300-2023 "Test Method for Pure Water Flux of Ceramic Flat Sheet Membranes". The results showed that the water flux decreased from the original 900 LMH to 860 LMH and 855 LMH after alkali treatment and acid treatment, respectively, with a decrease rate of 4.4% and 5.0%, respectively.

[0075] In a high-temperature flue gas filtration simulation experiment at 800℃, the membrane structure remained intact after undergoing 10 cycles of rapid cooling and heating (800℃↔ room temperature).

[0076] Example 3: Preparation of a thin-film asymmetric silicon carbide nanofiltration membrane for gas separation 1. Raw material preparation: The difference from Example 1 is as follows: In step 1, the transition layer slurry is made of 2μm β-SiC powder as the main skeleton (60wt%), with 5wt% sucrose (as a carbon source) and 10wt% silica sol (SiO2·nH2O, as a silicon source, with a solid content of 25~30%) added, as well as 25wt% organic solvent (a mixed solvent of ethanol and isopropanol, with a mass ratio of 3:2).

[0077] Separation layer slurry: The main raw materials are β-SiC fine powder (40wt%) with an average particle size of 80nm and polymethylsilane (PMS, 30wt%), with PMS serving as both a silicon-carbon precursor and a binder; 20wt% of a specific solvent (xylene) and 10wt% of the dispersant trioleyl ester are also added.

[0078] 2. Molding: The support slurry is extruded to form a flat film support (6mm thick, with a square channel in the middle with a side length of 2mm); a transition slurry (0.5mm thick) and a separation layer slurry (0.2mm thick) are sequentially cast onto the flat film support to form a thin, asymmetrical, three-layer stacked flat wet preform.

[0079] The aforementioned flat, three-layer stacked wet billet was microwave-dried in a tunnel-type continuous microwave drying line with the following parameters: microwave power 1.5kW, frequency 2450MHz, hot air temperature 60℃, and drying time 40min. After drying, the moisture content of the billet was reduced to below 3%.

[0080] 3. Sintering: The dried green body is placed in a graphite furnace and sintered in one piece under the protection of flowing argon gas. The heating program is as follows: heat to 800℃ at 1℃ / min (to fully crosslink and decompose PMS into amorphous SiC) and hold for 2 hours, then heat to 1550℃ at 3℃ / min and hold for 2 hours (to achieve the carbothermic reduction reaction of silica sol / sucrose and the crystallization of PMS-derived SiC), and finally heat to 1950℃ at 5℃ / min and hold for 1.5 hours (to promote the recrystallization and densification of nano-SiC grains) to obtain a thin-layer asymmetric silicon carbide nanofiltration membrane.

[0081] 4. Results and Characterization: Figure 3 This is a cross-sectional scanning electron microscope image of the obtained thin-layer asymmetric silicon carbide nanofiltration membrane. Figure 3 The results show that the pore size exhibits a continuous gradient change from the support layer to the separation layer, with no visible interface between the layers, and the thickness of the separation layer can be controlled within 200 μm.

[0082] The most probable pore size of the separation layer of the thin-layer asymmetric silicon carbide nanofiltration membrane was determined to be 2 nm using the gas bubble pressure method, which is within the nanofiltration range.

[0083] The porosity of the final thin-film asymmetric silicon carbide nanofiltration membrane was 42%, as measured by GB / 39717 2020.

[0084] The three-point bending strength of the thin-layer asymmetric silicon carbide nanofiltration membrane, as tested according to GB / T 1965, is 90 MPa.

[0085] Nitrogen gas flux testing was conducted according to GB / T 40260-2021, "Test Methods for Gas Permeation Performance of Polymer Membrane Materials". After immersing the thin-layer asymmetric silicon carbide nanofiltration membrane in strong acid (concentrated hydrochloric acid) for one week, the nitrogen gas flux decreased from 1100 LMH to 1080 LMH, with a nitrogen gas flux retention rate exceeding 98%, demonstrating its excellent chemical stability and the reliability of its seamless structure.

[0086] Thin-layer asymmetric silicon carbide nanofiltration membranes were boiled in 1M NaOH or 1M H2SO4 solutions for 24 hours. No peeling or bubbling of the membrane layer was observed. The water flux decreased from the original 400 LMH to 390 LMH and 385 LMH, respectively, with attenuation rates of 2.5% and 3.75%, respectively.

[0087] In a high-temperature flue gas filtration simulation experiment at 800℃, the membrane structure remained intact after undergoing 10 cycles of rapid cooling and heating (800℃↔ room temperature).

[0088] According to GB / T 40260-2021 "Test Method for Gas Permeation Performance of Polymer Membrane Materials" and related literature, the H2 / N2 mixed gas separation factor of the thin-layer asymmetric silicon carbide nanofiltration membrane was tested. The specific test procedure is as follows: Test Principle and Reference Standard: The gas separation membrane material evaluation method specified in GB / T 40260-2021 "Test Method for Gas Permeability Performance of Polymer Membrane Materials" (hereinafter referred to as the standard) is followed. The test uses the constant pressure variable volume method, establishing a pressure difference across the membrane to allow the mixed gas to permeate through it. The concentrations of H2 and N2 in the feed gas, residual gas, and permeate gas are measured separately using a gas chromatograph, and the separation factor is then calculated. This test method is also applicable to the gas separation performance evaluation of ceramic membranes (including silicon carbide ceramic membranes).

[0089] Test Apparatus and Conditions: A high-temperature gas separation membrane test system was used. The membrane tank was made of high-temperature resistant stainless steel (SUS316L), and the outer wall of the membrane tank was wrapped with a resistance heating furnace. Precise temperature control was achieved through thermocouples and a temperature controller, with an accuracy within ±1℃. The test temperature was set at 300℃. The test apparatus mainly consisted of the following parts: (1) Gas supply system: High-purity hydrogen (99.999%) and high-purity nitrogen (99.999%) are depressurized by a pressure reducing valve and then the flow rate is precisely controlled by a mass flow controller (MFC). They are then mixed in a preset ratio to form a H2 / N2 mixed gas with a specified molar ratio as raw material gas.

[0090] (2) Membrane testing assembly: A custom-made stainless steel flat membrane tank is used, with an effective test diameter of 40mm (adjustable according to the actual membrane size) and an effective test area of ​​12.56cm². 2 The membrane to be tested is placed in the membrane chamber, and sealing rings (such as graphite gaskets or PTFE gaskets) are installed on both sides of the membrane chamber to ensure airtightness. A temperature sensor is equipped at the air inlet of the membrane chamber, with a temperature control accuracy of ±0.1℃.

[0091] (3) Pressure control system: The pressure on the upstream side (feed gas side) of the diaphragm is regulated by a back pressure valve, while the downstream side (permeate gas side) is kept at atmospheric pressure. The pressure difference between the upstream and downstream sides is monitored by a precision pressure gauge or a digital pressure gauge. During the test, the upstream pressure is maintained at 0.2~0.5MPa, and the downstream pressure is about 0.1MPa.

[0092] (4) Gas analysis system: The raw material gas, residual gas (retained gas) and permeate gas are respectively connected to the gas chromatograph for gas concentration analysis. The pipeline is equipped with a three-way valve, which can switch the gas flow direction as needed.

[0093] Test operation steps: i. Sample preparation: Cut the thin-layer asymmetric silicon carbide nanofiltration membrane into a circular membrane sheet (approximately 45-50 mm in diameter) suitable for the membrane cell size, ensuring the membrane sheet is flat, wrinkle-free, and undamaged. Place the membrane sheet in the membrane cell, tighten the membrane cell cover, and seal it tightly with a sealing ring.

[0094] ii. System airtightness check: Close the downstream outlet of the membrane tank, introduce nitrogen gas upstream to pressurize to 0.6 MPa, maintain for 30 minutes, and observe the pressure drop. If the pressure drop is less than 5 kPa, the system is considered to have good airtightness.

[0095] iii. Pretreatment and Stabilization: High-purity nitrogen gas was continuously introduced upstream of the membrane at a flow rate of 50 mL / min to raise the system temperature to 300℃ and maintain this temperature for 60 min to remove adsorbed moisture and impurities from the membrane surface. After the temperature stabilized, the nitrogen gas was switched to an H2 / N2 mixture (molar ratio 1:1), and the system was pre-run for 60 min at a test temperature of 300℃ and an upstream pressure of 0.3 MPa to ensure that the system reached a stable permeation state.

[0096] iv. Permeate Gas Collection and Analysis: After the permeate reaches a steady state (typically defined as a fluctuation of less than 2% in three consecutive measurements of the permeate composition), the permeate gas is fed through the six-way valve sampling loop of the gas chromatograph via a three-way valve to collect the permeate gas sample for gas chromatograph analysis, recording the mole fractions of H2 and N2. Simultaneously, feed gas and residual permeate gas samples are collected and analyzed separately. Each sample is measured three times, and the average value is taken as the final analytical result.

[0097] v. Permeation Flux Measurement: The volumetric flow rate of the gas on the permeate side per unit time is measured using a soap bubble flow meter or mass flow meter. A soap bubble flow meter is connected to the permeate outlet to measure the time required for the gas to pass through a specific volume (e.g., 1 mL), the permeate flow rate (mL / min) is calculated, and then converted to the permeate flow rate (cm³) under standard conditions. 3 (STP) / s).

[0098] vi. Data recording and calculation: Record the feed gas flow rate, upstream and downstream pressure, test temperature, and mole fraction of each gas component, and calculate the permeability, permeation flux, and separation factor according to the formula.

[0099] Calculation of the separation factor: According to standards and literature definitions, the separation factor α(i / j) of component i to component j in a gas mixture is defined as the ratio of the mole fractions of the two gas components on the permeate side (or the osmotic side), and the specific formula is as follows: α H2 / N2 = ( x H2 / x N2) / ( y H2 / y N2).

[0100] Since the molecular size of H2 (kinetic diameter of about 0.289 nm) is significantly smaller than that of N2 (kinetic diameter of about 0.364 nm), silicon carbide nanofiltration membranes, which use molecular sieving as the main separation mechanism, have higher permeation selectivity for H2.

[0101] Test results: The thin-layer asymmetric silicon carbide nanofiltration membrane obtained in Example 3 was tested for H2 / N2 mixed gas separation performance at 300°C. The H2 / N2 molar ratio of the feed gas was 1:1, the upstream pressure was 0.3 MPa, and the downstream pressure was 0.1 MPa. Gas chromatography analysis showed that the molar fraction of H2 in the permeate gas was 93.8%, the molar fraction of N2 was 6.2%, and the molar fractions of H2 and N2 in the feed gas were each 50%. The separation factor was calculated using the above formula as αH2 / N2≈15. The permeability of pure H2 gas was also measured to be approximately 2.5 × 10⁻⁶. -7 mol·m -2 ·s -1 ·Pa -1 The permeability of pure N2 gas is approximately 1.7 × 10⁻⁶. -8 mol·m -2 ·s -1 ·Pa -1 The calculated ideal separation factor is approximately 14.7, which is in good agreement with the separation factor of the mixed gas, confirming the reliability of the test results.

[0102] Comparative Example 1: Preparation of silicon carbide films using the traditional stepwise sintering method 1. Preparation of the support: The support slurry composition is: 65wt% α-SiC coarse powder (50μm), 5wt% flake graphite, 10wt% silicon powder (325 mesh), and 20wt% organic system (5% PVB binder, 2% castor oil phosphate dispersant, 3% DBP plasticizer, and 10% ethanol solvent). After the above components are ball-milled and mixed evenly, the mixture is extruded to obtain a tubular support wet blank. After drying, it is sintered at 2100℃ under an argon atmosphere for 2 hours to obtain a pre-sintered support.

[0103] 2. Preparation of the separation layer slurry: The separation layer slurry consists of 50wt% β-SiC fine powder (0.5μm), 10wt% phenolic resin, 15wt% nano-silica powder (~100nm), and 25wt% organic system (5% trioleic acid glyceride dispersant and 20% toluene solvent).

[0104] 3. Film coating and secondary sintering: The separation layer slurry is dipped onto the surface of the pre-sintered support and dried at room temperature. Then, a second sintering is carried out at 1900℃ in an argon atmosphere for 1 hour to densify the film layer and obtain a silicon carbide film.

[0105] Figure 4 The image shows a cross-sectional scanning electron microscope image of the obtained silicon carbide film. Figure 4 It can be seen that there are obvious physical interfaces and defects between the film layers.

[0106] The porosity of the final silicon carbide film, as measured by GB / 39717 2020, was 40%.

[0107] The three-point bending strength of the silicon carbide film, as tested according to GB / T 1965, was only 45 MPa.

[0108] The silicon carbide membrane was boiled in 1M NaOH or 1M H2SO4 solution for 24 hours. No peeling or bubbling occurred in the membrane. The water flux decreased from the original 1500 LMH to 1450 LMH and 1440 LMH, respectively, with attenuation rates of 3.3% and 4%.

[0109] In a high-temperature flue gas filtration simulation experiment at 800℃, after undergoing 10 cycles of rapid cooling and heating (800℃↔ room temperature), the membrane layer showed local peeling.

[0110] By comparing Comparative Example 1 with Example 1, the significant advantages of the method of the present invention in achieving "seamless connection" between layers, improving the overall performance of the product, and simplifying the process are fully demonstrated.

[0111] Comparative Example 2: Gradient green body but sintered in stages The difference from Example 3 is that in step 3, the dried green body was placed in a graphite furnace and sintered directly at 2050°C for 2 hours under flowing argon protection, with the temperature increased from room temperature to 2050°C at a rate of 5°C / min (simulating traditional recrystallization sintering, where recrystallization alone is insufficient to achieve sufficient densification of the nanolayers). After cooling, a green body with a loose structure and powdered separation layers was obtained. This step demonstrates that for nanoscale functional layers, simple high-temperature recrystallization cannot achieve effective sintering in one step.

[0112] The failure stemmed from the significant difference in sintering kinetics between the coarse particles in the support layer and the nanoparticles in the separation layer during the one-step high-temperature sintering process. This resulted in substantial internal stress generated during the rapid removal of the organic binder and the potential abnormal growth of the nanoparticles, leading to cracking and pulverization of the functional layer. This underscores the ingenuity and necessity of the sequential integrated sintering process of this invention: "first, a medium-temperature in-situ reaction to build a bridge, followed by high-temperature recrystallization for strengthening."

[0113] Comparative Example 3: Preparation of silicon carbide films by integrated sintering but lacking in-situ reaction sources In step 1, the support slurry is made by adding 40 wt% organic solvent ethanol to 50 μm β-SiC powder as the main skeleton (60 wt%).

[0114] Transition layer slurry: 2μm β-SiC powder as the main skeleton (60wt%), with 40wt% organic solvent added (a mixture of ethanol and butanone in a mass ratio of 1:1).

[0115] Separation layer slurry: 40 wt% of β-SiC fine powder with an average particle size of 0.1 μm was added to an organic system (55 wt% xylene and 5 wt% trioleic acid glyceride dispersant).

[0116] Steps 2 and 3 are the same as in Example 3.

[0117] After sintering, although each layer in the silicon carbide film has a certain strength, the interlayer bonding force is weak, and it is only a physical stack. The separation layer can be peeled off from the support by hand.

[0118] This comparison shows that relying solely on physical contact and high-temperature evaporation-condensation mass transfer (recrystallization) results in limited material transport efficiency at the interlayer interface, insufficient to form strong chemical bonds. The in-situ reaction introduced in this invention generates a large number of highly active SiC whiskers or nanoparticles in the interfacial region. These newly formed phases, like "rivets," penetrate the initial interface, providing abundant nucleation sites and material transport channels for subsequent recrystallization bonding, which is the chemical basis for achieving "seamless bonding."

[0119] Comparative Example 4 The difference from Example 3 is that the sintering process in step 3 is adjusted as follows: the temperature is increased from room temperature to 300°C at a rate of 2°C / min, then increased from 300°C to 500°C at a rate of 0.5°C / min, then increased to 600°C at a rate of 2°C / min, and held at that temperature for 3 hours. Finally, the temperature is naturally cooled to room temperature. Other conditions are the same as in Example 3, and a planar silicon carbide ultrafiltration membrane is obtained.

[0120] The average pore size of the separation layer of the planar silicon carbide ultrafiltration membrane was measured to be 50 nm using the bubble pressure method, making it suitable for applications such as oil-water emulsion separation.

[0121] The porosity of the obtained planar silicon carbide ultrafiltration membrane was 40%, as measured by GB / 39717 2020.

[0122] The three-point bending strength of the flat silicon carbide ultrafiltration membrane, as tested according to GB / T 1965, is 50 MPa.

[0123] When the flat-sheet silicon carbide ultrafiltration membrane was boiled in 1M NaOH or 1M H2SO4 solution for 24 hours, there was no peeling or bubbling of the membrane layer. The water flux decreased from the original 700 LMH to 672 LMH and 658 LMH, respectively, with attenuation rates of 4% and 6%.

[0124] In a high-temperature flue gas filtration simulation experiment at 800℃, the membrane structure remained intact after undergoing 10 cycles of rapid cooling and heating (800℃↔ room temperature).

[0125] Through comparison with embodiments and comparative examples, the technical solution of the present invention has the following advantages: (1) Traditional stepwise sintering (Comparative Example 1) inevitably produces weak interfaces; and even if integrated sintering is used, if there is a lack of in-situ reaction source (Comparative Example 3) or improper sintering regime (Comparative Example 2), it is impossible to achieve a strong interlayer bond.

[0126] (2) This invention achieves a “seamless connection” between the support and the film layer through the synergistic effect of “reactive raw material system”, “gradient co-forming” and “reaction-recrystallization sequential integrated sintering”. None of these three elements can be omitted.

[0127] (3) Significant performance advantages: The ceramic membranes prepared by this invention (Examples 1-3) show comprehensive and leapfrog improvements in mechanical strength, environmental reliability (thermal shock resistance, corrosion resistance) and precise pore size control, perfectly solving the pain points of the industry.

[0128] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing silicon carbide ceramic films by reaction-recrystallization integrated sintering, characterized in that, Includes the following steps: A first silicon carbide powder, a first carbon source, a first silicon source, an organic binder, a first dispersant, a plasticizer, and a first organic solvent are mixed to obtain a support slurry; the mass percentage of the first carbon source in the support slurry is 0.5% to 5%. The second silicon carbide powder, the second carbon source, the second silicon source, and the second organic solvent are mixed to obtain a transition layer slurry. The third silicon carbide powder, the third carbon source, the third silicon source, the second dispersant, and the third organic solvent are mixed to form a separation layer slurry; After the support slurry, transition layer slurry and separation layer slurry are co-formed, they are microwave dried to form a green body in which the support slurry, transition layer slurry and separation layer slurry are stacked in sequence. The green body is subjected to reaction-recrystallization integrated sintering to obtain the silicon carbide ceramic film; The reaction-recrystallization integrated sintering procedure is as follows: The temperature is first raised from room temperature to a first temperature and then kept warm for a first time. The first temperature is 600~1400℃ and the first warming time is 2~4h. The temperature is raised from the first temperature to a second temperature and then kept warm for a second time. The second temperature is 1400~1800℃ and the second holding time is 1~2 hours. The temperature is raised from the second temperature to a third temperature and then held for a third time. The third temperature is 1900~2150℃ and the third holding time is 1.5~2h. The particle size of the first silicon carbide powder is greater than that of the second silicon carbide powder, which is greater than that of the third silicon carbide powder. The support slurry comprises the following components by mass percentage: The first component is 60-65% silicon carbide powder, the first carbon source is 0.5-5%, the first silicon source is 5-10%, the first organic binder is 1-5%, the first dispersant is 0.5-3%, the first plasticizer is 1-5%, and the first organic solvent is 10-20%. The first silicon carbide powder is α-SiC, and the particle size of the first silicon carbide powder is 20~100μm; the first carbon source includes one or more of carbon black, graphite and phenolic resin; the first silicon source includes silicon powder. The transition layer slurry comprises the following components by mass percentage: The second silicon carbide powder comprises 40-60%, the second carbon source comprises 5-30%, the second silicon source comprises 10%, and the second organic solvent comprises 20-25%. The second silicon carbide powder is α-SiC powder or β-SiC powder, and the particle size of the second silicon carbide powder is 1~10μm; the second carbon source includes one or more of sucrose, phenolic resin and carbon black; the second silicon source includes silicon powder and / or silica sol. The separation layer slurry comprises the following components by mass percentage: The third component is 40-50% silicon carbide powder, the third component is 1-10% carbon source, the third component is 15-30% silicon source, the second component is 0.5-10% dispersant, and the third component is 15-25% organic solvent; The third silicon carbide powder is β-SiC powder, and the particle size of the third silicon carbide powder is 0.05~1μm; the third carbon source includes carbon black and / or phenolic resin; the third silicon source includes one or more of silicon powder, polymethylsilane and vinyl perhydropolycarbosilane; The co-molding method is one or more of co-extrusion molding, sequential casting molding, and pressure-assisted injection molding.

2. The method according to claim 1, characterized in that, The reaction-recrystallization integrated sintering is carried out under a protective atmosphere, namely argon.

3. The method according to claim 1, characterized in that, The heating rates of the first, second, and third heating are independently 1~10℃ / min.

Citation Information

Patent Citations

  • Pure silicon carbide ceramic membrane component and preparation method thereof

    CN108261928A

  • Ultralow-temperature co-sintering preparation method and application of high-flux silicon carbide ceramic membrane

    CN117820007A

  • Preparation of oriented hole silicon carbide porous ceramic

    CN101323524A

  • Silicon carbide ceramic membrane suitable for sponge city and preparation method of silicon carbide ceramic membrane

    CN115385714A

  • One-step co-fired silicon carbide plate ceramic membrane based on digital light processing and preparation method thereof

    CN116283300A